Dormancy in Plants From Whole Plant Behaviour to Cellular Control - Viemont, J. D.; Crabbe, J.; Ebooks Corporation (Wallingford : CABI, 2000)
Understanding plant dormancy is of great importance to sustainable and efficient plant and crop growth. This book has been developed from papers presented at the 2nd International Symposium on Plant Dormancy held in Angers in July 1999. It contains research material on the subject.
Contenido: 8 Water Relations in Winter: Effect on Bud Break of Walnut Tree9 Morphological Structure and Water Status in Tulip Bulbs during their Transition from Dormancy to Active Growth: Visualization by Magnetic Resonance Imaging; 10 Seed Dormancy as One of the Survival Strategies in Annual Plant Species Occurring in Deserts; 11 Seasonally Regulated Proteins in Peach (Prunus persica L. Batsch): What A
Libro electronico adquirido a perpetuidad con la editorial CABI
Keywords: DORMANCIA EN PLANTAS